Mechanical and corrosion properties of newly developed biodegradable Zn-based alloys for bone fixation - Vojtěch, D; Kubásek, J; Serák, J; Novák, P (Acta biomaterialia, 2011)
In the present work Zn-Mg alloys containing up to 3wt.% Mg were studied as potential biodegradable materials for medical use. The structure, mechanical properties and corrosion behavior of these alloys were investigated and compared with those of pure Mg, AZ91HP and casting Zn-Al-Cu alloys. The structures were examined by light and scanning electron microscopy (SEM), and tensile and hardness testing were used to characterize the mechanical properties of the alloys. The corrosion behavior of the materials in simulated body fluid with pH values of 5, 7 and 10 was determined by immersion tests, potentiodynamic measurements and by monitoring the pH value evolution during corrosion. The surfaces of the corroded alloys were investigated by SEM, energy-dispersive spectrometry and X-ray photoelectron spectroscopy. It was found that a maximum strength and elongation of 150MPa and 2%, respectively, were achieved at Mg contents of approximately 1wt.%. These mechanical properties are discussed in relation to the structural features of the alloys. The corrosion rates of the Zn-Mg alloys were determined to be significantly lower than those of Mg and AZ91HP alloys. The former alloys corroded at rates of the order of tens of microns per year, whereas the corrosion rates of the latter were of the order of hundreds of microns per year. Possible zinc doses and toxicity were estimated from the corrosion behavior of the zinc alloys. It was found that these doses are negligible compared with the tolerable biological daily limit of zinc.
Keywords: fotoelektronová spektroskopie; testování materiálů; Spectrometry, X-Ray Emission; mikroskopie elektronová rastrovací; ortopedické fixační pomůcky; biokompatibilní materiály; zinek; Biocompatible Materials; Photoelectron Spectroscopy; Materials Testing; Zinc; Microscopy, Electron, Scanning; Orthopedic Fixation Devices; Corrosion; slitiny; koroze; Alloys; spektrometrie rentgenová emisní